Pengaruh Penerapan Model Numbered Head Together (NHT) Terhadap Hasil Belajar pada Mata Pelajaran Informatika Kelas IX di SMP Negeri 29 Padang (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the Numbered Heads Together (NHT) cooperative learning model on the learning outcomes of students in Grade IX Informatics at SMP Negeri 29 Padang. Initial observations showed that most students were still passive, lacked enthusiasm, their learning outcomes were below the minimum competency standard, and the learning process tended to be teacher-centred. The research used a quantitative approach with a quasi-experimental design, with class IX.8 as the experimental class and IX.6 as the control class, each consisting of 31 students selected through purposive sampling. The research instrument consisted of 25 multiple-choice questions that had been tested for validity and reliability. Data analysis was conducted using normality tests and Mann Whitney U non-parametric tests. The results showed that the average score of the experimental class was 77.54, which was higher than that of the control class, which was 66. The Asymp. Sig (2-tailed) value of 0.001 < 0.05 indicated a significant effect. Thus, the application of the NHT learning model has an effect on improving student learning outcomes.